2022-RA-983-ESGO Anal high-grade intraepithelial neoplasia in women with cervical high-grade intraepithelial neoplasia. (20th October 2022) - Viscardi, Anna; Salmaso, Marta; Alberico, Daniela; Loreto, Eugenia Di; Libutti, Giada; Roncella, Elena; Cetera, Giulia Emily; Boero, Veronica; Barbara, Giussy; Monti, Ermelinda
Abstract : Introduction/Background: Anal high-grade intraepithelial neoplasia (AIN2–3) is the precursor of HPV-related anal cancer. Although anal cancer is rare, its incidence is rising, especially in women. Women with high-grade cervical neoplasia (CIN2–3) or HPV-related genital cancer are at increased risk of developing AIN. Other risk groups include people living with HIV, immunocompromised patients, and Men who have Sex with Men (MSM). Methodology: The objective of this monocentric prospective study was to analyze the prevalence of AIN2–3 among women treated for CIN2–3. Exclusion criteria were: age <25 years, previous HPV vaccination, immunosuppression, HIV infection and a history of anorectal cancer. All patients enrolled in the study underwent anal cytology and anal high-risk HPV-DNA testing (aHPV-DNA). If one or both tests were positive a high-resolution anoscopy with biopsy of suspicious lesions was performed. All women also completed a questionnaire on a sexual habit. Results: A total of 100 women were enrolled between 2019 and 2021. Among these, eight patients had a concomitant or past diagnosis of anogenital warts, while one patient had a previous diagnosis of VaIN-HSIL. Anal Pap smears were positive for low-grade lesions in three patients, while 73 women tested positive for aHPV-DNA. Histological examination revealed the presence of AIN2–3 lesions in four patients, who subsequently underwent excisional treatment. Although 50% of aHPV-DNA positive women reported having anal intercourse, as many as 45% of these declared they used condoms. Conclusion: Women with CIN2–3 are at high-risk of developing AIN2–3, although to date no recommendations regarding prevention and treatment of AIN in this group of patients are available. Barrier methods aren't always effective to prevent anal HPV infection, probably due to the fact that the cervix is a reservoir of the infection.